"How nationality influences Opinion": Darwinism and palaeontology in France (1859–1914). (December 2017) - Cohen, Claudine
Abstract: This paper discusses the "non-reception" of Darwin's works and concepts in French palaeontology and palaeoanthropology between 1859 and 1914. Indeed, this integration was difficult, biased and belated, for ideological, intellectual and epistemological reasons: Clémence Royer's biased 1862 translation of Darwin's Origin of Species pulled its ideas toward "social darwinism", making them less attractive to the natural sciences. - French nationalism and the authority of religion, which imposed Cuvier's thinking until late into the century - the dominance of Lamarckian and neo-Lamarckian transformism in France, both in biology and in paleontology, which proposed the notion of orthogenetic laws and environmental determinations, and refused darwinian evolutionary mechanisms - obstacles inherent to the application of Darwin's concepts to palaeontology, namely the impossibility to identify evolutionary mechanisms through the fossil record, which was stressed by Darwin himself and underlined in turn by 19th century French palaeontologists. However, as I argue, in the course of the examined period, French palaeontology grew from refusal to a better understanding and evaluation of Darwin's thinking. The quest for intermediary forms, the construction of branching evolutionary trees and the attempts to reconstruct human biological and cultural evolution were important efforts toward an integration of some aspects of Darwinian views and practices into French palaeontology and plaeoanthropology. The 1947 Paris conference which brought together American Neo-darwinists and French paleontologists made Darwinian concepts better understood and triggered a revival of French palaeontology from the 1960s. Highlights: Analyzes different aspects of 19th century French anti-Darwinism, their causes and effects. Describes the emergence of transformist views in French late 19th-Century palaeontology. Examines the specificity of French Neo-Lamarckian thought. Studies the reference to Darwin's thought in 19th century French palaeontological works (Gaudry, Saporta, Deperet, F. Bernard). Studies evolutionary concepts involved in the approach to Human evolution.